2009
DOI: 10.1016/j.virusres.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus receptors and their implications in gene delivery

Abstract: Adenoviruses (Ads) have gained popularity as gene delivery vectors for therapeutic and prophylactic applications. Ad entry into host cells involves specific interactions between cell surface receptors and viral capsid proteins. Several cell surface molecules have been identified as receptors for Ad attachment and entry. Tissue tropism of Ad vectors is greatly influenced by their receptor usage. A variety of strategies have been investigated to modify Ad vector tropism by manipulating the receptor-interacting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 184 publications
(233 reference statements)
2
92
0
3
Order By: Relevance
“…[6] There are over 100 adenoviral serotypes identified that can infect and replicate in a wide range of organs, including 51 classified into six subgroups (A-F). [38,39] Of these, serotypes 2 and 5 in subgroup B are the most characterized viruses.…”
Section: Adenoviral Vectors-mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] There are over 100 adenoviral serotypes identified that can infect and replicate in a wide range of organs, including 51 classified into six subgroups (A-F). [38,39] Of these, serotypes 2 and 5 in subgroup B are the most characterized viruses.…”
Section: Adenoviral Vectors-mentioning
confidence: 99%
“…Viral fibre proteins bind to the Coxsackievirus and adenovirus receptor of the target cells to initiate the infection. [39,44] Internalization occurs via receptor-mediated endocytosis followed by release from the endosome. [45] Once inside the cytoplasm, the viral capsid undergoes disassembly as it migrates to the nuclear pore.…”
Section: Adenoviral Vectors-mentioning
confidence: 99%
“…To date, more than 100 adenovirus serotypes have been classified, of which 51 serotypes are human adenoviruses, divided into seven species (human adenovirus A to F). These classifications are based on their hemagglutination properties, oncogenic potential in newborn hamsters, genomic organization and DNA homology (Sharma et al, 2009). Adenoviruses are non-enveloped, icosahedral viruses of 80 to 1200 nm in diameter.…”
Section: Adenoviruses As a Gene Transfer Vectormentioning
confidence: 99%
“…The double stranded DNA genome is located in the virion core with DNA associated proteins and terminal proteins that serve as a primer for DNA replication. Human adenoviruses are known to cause a variety of clinical symptoms, depending on their serotypes (Sharma et al, 2009). These include infections of the upper and lower respiratory tract, renal and urinary tract, gastroenteritis and ocular infections.…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation